PERKEMBANGAN PERIKANAN BUDIDAYA DAN KONTRIBUSINYA DI SEKTOR PERTANIAN DALAM PEREKONOMIAN KABUPATEN LIMA PULUH KOTA, SUMBAR. - Ramli, M (Jurnal Perikanan dan Kelautan, 2009)
This research aims to see fishery development and the parts at agriculturalsector in Lima Puluh Kota regency economics. Analysis results is known duringfive development the last year aquaculture area decreased, but so the productionincreases. Pool vast average goes down 0,85%, minapadi go down 36,27%,karamba go down 19,72%, longyam go down 6,68%, temporary productionincreases 13,06%. Year 2007 fishery product 6.137,8 tons with products valuesRp 114.049,30,- million or as big as 7,86% from agricultures totals productsvalues (Rp 1.451.373,73,-). Fisheries subsectors contributions in PDRBs 2,72%,equal buildings sectors contributions (2,85%) above financial, rental, companysector contribution (2,47%, and electricity, gas, clean water sector (0,43%)